Waqf as an Alternative Financing for Solar Energy in Indonesia: Opportunities and Challenges (ZISWAF: Jurnal Zakat dan Wakaf, 2024)
The problem of environmental damage is a global problem that must be addressed immediately for the survival of humans and other living things on earth. The best way to solve this problem is by switching to renewable energy (RE). However, this transition requires a high cost, so alternative financing is needed. Waqf can be alternative financing to fund RE. The most potential renewable energy is solar energy because it is relatively low installation costs, easy to install, and is suitable for tropical areas such as Indonesia. Some studies proposed the concept of energy financing, but none have proposed waqf as an alternative to energy financing, especially solar energy. This paper aims to determine the opportunities and challenges of waqf as an alternative to financing solar energy in Indonesia based on the practice. The research data were obtained from literature studies and in-depth interviews with energy waqf stakeholders in Indonesia. The results show that waqf has a great opportunity as an alternative for financing solar energy in Indonesia, but the biggest challenge is the lack of socialization and education on waqf and solar energy. This research can be used as a consideration for policymakers.